Entangled life : how fungi make our worlds, change our minds and shape our futures - Sheldrake, Merlin (Vintage, 2021)
"The more we learn about fungi, the less it makes sense without them. They can change our minds, heal our bodies and even help us avoid environmental disaster; they are metabolic masters, earth-makers and key players in most of nature's processes. In Entangled Life, Merlin Sheldrake takes us on a mind-altering journey into their spectacular world, and reveals how these extraordinary organisms transform our understanding of our planet and life itself."--From back cover.